Western flute, dizi, and bansuri flute playing practices and teaching methods from the viewpoint of selected practitioners in Kuala Lumpur - Chai, Yem Voon (2015)
Living in a multicultural country like Malaysia, chances being exposed to experiences with different social and ethnic cultures are rather high in every aspect of life. From the basic need of life such as eating and living in the same neighbourhood, especially urban Malaysians cannot escape intercultural processes through their daily experience. Many of the joint spaces and situations may involve a wider field of intercultural impact. Cultural properties and connected views are outcomes of former and ongoing global exchange patterns that started in colonial times. Musical instruments played in present day Malaysia are musical instruments coming from cultures outside Malaysia. Flutes illustrate this situation very clearly. Though on the territory of present day Malaysia exist a number of indigenous flute playing practices that also include performance and transmission, the flutes that are performed and taught most are brought to Malaysia from Europe, that is referred to as western flute, from China (dizi), and from India (bansuri). Considering that Malaysia is a country in which music education is apparently less privileged compared to other teaching subjects, the general understanding towards music is rather mono-cultural though an acceptance towards diverse music practices of local origin can be noted. However, the active and wellestablished professional orchestras like Malaysian Philharmonic Orchestra (MPO) and Malaysian National Symphony Orchestra (MNSO) are the top models in playing western classical music in the country. Likewise, there is no professional Chinese orchestra but a number of Chinese orchestras playing Chinese traditional music on amateur level while there is no Indian orchestra yet at the moment as orchestras as such are not an Indian tradition. Based on the recent concerts happening in Kuala Lumpur, it seems that all ensembles are working well independently and thus crossover cooperation All material contained within the thesis, including without limitation text,logos, icons, photographs and all other artwork, is copyright material of Universiti Putra Malaysia unless otherwise stated. Use may be made of any material contained within the thesis for non-commercial purposes from the copyright holder. Commercial use of material may only be made with the express, prior, written permission of Universiti Putra Malaysia. Based on the recent concerts happening in Kuala Lumpur, it seems that all ensembles are working well independently and thus crossover cooperation does not seem being a necessity as the actual environment in Kuala Lumpur is discouraging intercultural activities. This is obvious when it comes to music learning especially on instruments which are symbolizing social and ethnic attachments. For instance, particular instruments are only learnt by the specific community to which they belong. For example, western flute is learnt in the school band or school orchestra by everyone, but Chinese dizi in a Chinese orchestra and Indian bansuri is taught only in the Temple of Fine Arts. Western flute is more widely promoted in the society since the number of bands and orchestras in need of flutists is far higher that the performance options of the other two flutes, though performance and the concert possibilities exist thus generally a platform to perform is available to all. However, at the same time, there are very few performance opportunities for Indian bansuri and Chinese dizi. Looking at the wider picture, music performances in Kuala Lumpur are not as widely promoted and considered economically necessary as in other large Asian metropoles. If music performances are generally regarded less necessary, the question is how to prevent extinction of diverse flute playing cultures and how to encourage cultural exchange at the same time. This thesis aims at exploring the way of approaching western flute, dizi and bansuri, their cultural context, performance practice and transmission methods. The cultural position of “flute players” and their learning situation in Malaysia will be covered from the viewpoint of selected practitioners. Finally, applications of flute playing in live performances will have to be observed and analysed as well as transmission methods that may give an insight on flute playing practices in Kuala Lumpur. Investigating transmission methods has to mainly focus on teaching materials used, class structures in terms of participants and sequence of teaching units. This is to understand the different social and cultural contexts of performance practice as well as the transmission methods of the three types of flutes and their mutual perpetuation as part of multi-layered culture.